TEACHERS’ INSTRUCTION USED BY ENGLISH TEACHERS AT MTs PANCASILA KOTA BENGKULU AN ANALYSIS OF SPEECH FUNCTIONS - Detti Lismayanti; Okti Liani (UNIVED Press, 2018)
The aims of this research are: 1) to know the speech functions manifested in English teachers’ instruction at MTs Pancasila Kota Bengkulu, and 2) to infer the dominant speech function used by English teachers at MTs Pancasila Kota Bengkulu. The design of this research is qualitative by applying descriptive method. The subjects of this research are two English teachers in MTs Pancasila Kota Bengkulu. The data was collected using recording and observation techniques. Besides that, the procedure of data analysis are; data reduction, data display, drawing conclusion and verification. All of the data that have classified was interpreted concerned with the description of the situation. The result of this research showed that: 1) the speech functions manifested in English teachers’ instruction at MTs Pancasila Kota Bengkulu were about 102 of speech function that summarized into 48 utterances, and 2) the dominant speech function used by English teachers at MTs Pancasila Kota Bengkulu is directive function, which are 61% utterances. Finally, in great expectation by applying this research data analysis, English teacher can see the benefits and understand how to use the speech function in the teaching-learning process. Keywords: Speech Function, Teachers’ Instruction